A cross-sectional study on the nutritional status and morbidity profile of tribal and non-tribal female brick-field workers of Paschim Medinipur district - Sujata Maiti Choudhury; Prasan Sabud; Pralay Maity; Madhubanti Bepari; Ananya Pradhan (Occupational Health and Safety Society of Nepal, 2016)
Objective: The aim of the present study was to investigate the socioeconomic, anthropometric status and health morbidity profile of tribal and non tribal female brick-field workers of Paschim Medinipur district. Study design: Assessment of socioeconomic, health and nutritional parameters were done using 300 tribal & non tribal brick-field female workers at the age group of 18-30 years after randomized sampling. Place and duration of study: The study was done in 30 brick-fields located in Paschim Medinipur district of West Bengal in the month of November and December, 2013 for a period of 60 days. Methodology: Through oral questionnaire methods, socioeconomic studies, health morbidity profile and dietary assessments were performed. Anthropometric parameters were measured by the conventional anthropometric methods. Results: From the study it was observed that most of the women workers were illiterate. Female workers of non tribal and tribal groups engaged in this industry were living below the poverty line and the tribal workers showed poor economic status than the non-tribal women workers. The female workers showed significant decrease in height, weight and body mass index, compared to the Indian national standard values. Mid upper arm circumference (MUAC) and waist-hip ratio (WHR) was also significantly lower to the Indian national standard in both age groups of female workers. The intake of energy, protein, carbohydrate carotene, riboflavin, dietary fiber, calcium and iron were significantly lower compared to the standard ICMR RDA. Conclusion: The female workers engaged in brick manufacturing works are mostly illiterate, economically backward, which make them vulnerable to health insecurity. Malnutrition among tribal & non tribal female workers is a problem that has perhaps been under-recognized, and should now take greater priority. International Journal of Occupational Safety and Health, Vol 4 No 2 (2014) 51 - 57